Torakochirurgia The use of argon plasma coagulation for treatment of malignant and nonmalignant airway stenoses - Grochowski, Zbigniew; Olechnowicz, Henryk; Czajkowski, Wojciech; Warmus, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Aim: To assess the feasibility of argon plasma coagulation (APC) in the endoscopic clearing of airway stenosis and in the management of bleeding into the bronchial tree. Material and methods: A total of 64 patients (F-25, M-39) were considered in this study; 82 procedures of clearing airway stenosis were performed. In 40 cases the interventions included bronchial stent implantations. In 36 patients indications for APC were airway obstruction and bleeding into the bronchial tree as a result of malignant tumours. In 28 patients APC was used to resect granuloma in the larynx and trachea due to intubation and tracheostomy. Results: In 56 patients (87.5%) an instantaneous improvement in ventilation parameters and stoppage of bleeding were observed. In 8 patients (12.5%) the ventilation parameters improved after 2-3 days. In 2 patients (3.1%) complications occurred, namely exacerbation of bleeding into the bronchial tree and a short flame in the airways. Conclusions: APC is an effective tool to reestablish airway patency and manage bleeding caused by benign and malignant lesions. However, considering the possibility of complications, this procedure should be undertaken by experienced specialists.